Development Of Building And Road Spatial Database For Parit Buntar New Township - Tg. Azhar, Tengku Noor Arbaee (Universiti Sains Malaysia, 2006)
The general scope of this project is the development of spatial database for road network system and building information of Parit Buntar New Township. The data capture process applies the utilization of satellite image of high resolution where road and building features can be extracted by means of screen digitization. Spatial database development was carried out using IDRISI GIS database workshop capability where all attributes regarding road network and building lots are obtained through field sampling process. The geo-relational data model that joins spatial data and attributes data was adopted in the development of database, as every spatial data are stored in graphic files while the attribute data are stored in table. There were linked through the features ID which is differentiated by color’s unique value. The final output of this project is a spatial database system that provides attribute and spatial information of Parit Buntar New Township. There seem to be a demand in the development of database as it will became the mechanism for residents to get information and as reference for future development which can be up dated easily.